2010
DOI: 10.1007/s10344-010-0488-4
|View full text |Cite
|
Sign up to set email alerts
|

Avian pox infection in different wild birds in India

Abstract: Amplicons of fpv167 and fpv140, of 578 and 1,800 bp, respectively, characteristic of the avipox viral genes, were amplified by PCR using DNA from viruses isolated from eight Indian wild birds. BLAST and phylogenetic analysis of the sequences of the fpv167 and fpv140 amplicons indicated that Fowlpox virus (FWPV) was the nearest phylogenetic neighbour to the viral isolates, from two Indian peacocks (Pavo cristatus), two golden pheasants (Chrysolophus pictus), one silver pheasant (Lopahura nycthemera) and one spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Poxviruses isolated from the African, Magellanic and Humboldt penguins group in Clades A2, A3 (FWPV-like) and B1 (CNPV-like) respectively [ 6 , 8 ]. Columbiformes have been shown to be susceptible to viruses from clade A (Fowlpox-like) [ 3 , 5 , 21 , 22 ] and clade B (Canarypox-like) [ 3 , 4 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Poxviruses isolated from the African, Magellanic and Humboldt penguins group in Clades A2, A3 (FWPV-like) and B1 (CNPV-like) respectively [ 6 , 8 ]. Columbiformes have been shown to be susceptible to viruses from clade A (Fowlpox-like) [ 3 , 5 , 21 , 22 ] and clade B (Canarypox-like) [ 3 , 4 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the hosts of the order Galliformes primarily harboured the A1 subclade, which is similar to the findings reported by Gyuranecz et al, and Jarmin et al, (Gyuranecz et al, ; Jarmin et al, ). Although subclade A1 was previously reported in India (Pawar et al, ), the host species were observed to be endangered wild birds sampled from the Indian states of Andhra Pradesh, Karnataka and Maharashtra. In this study, for the first time, we report the presence of subclade A1 in domesticated and economically important bird species of India.…”
Section: Discussionmentioning
confidence: 75%
“…Although subclade A1 was previously reported in India (Pawar et al, 2011), the host species were observed to be endangered wild birds sampled from the Indian states of Andhra Pradesh, Karnataka and Maharashtra. In this study, for the first time, we report the presence of subclade A1 in domesticated and economically important bird species of India.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Because of some APV strains may be found in several bird species the introduction of domestic birds may be a threat for wild birds, especially in isolated populations. Conversely, wild birds may be an infection source for poultry [5,11,12]. …”
Section: Introductionmentioning
confidence: 99%